Vivências de adolescentes com sintomas depressivos em contexto escolar - Fernando Fraga Herzog; Aline Cammarano Ribeiro; Lisiane dos Santos Welter; Graciela Dutra Senhem; Lidiana Batista Teixeira Dutra Silveira; Fernanda Franceschi Freitas (Universidade Federal de Santa Maria, 2020)
Objective: to know the experiences of adolescents with depressive symptoms in school context. Method: qualitative study carried out in a public school in the countryside of the state of Rio Grande do Sul. The interviewees were 05 adolescents with depressive symptoms or diagnosis of depression, according to a checklist. The interviews occurred from April to May 2019 and the data were treated by Content Analysis of Minayo. Results: two categories emerged from the adolescents' speeches: the adolescence and the intensification of the depressive symptoms and sources of support and the prospects for the future. Final Thoughts: the adolescents present common experiences for age, such as the interaction with the family, school and peers, as well as behaviors of indecision and doubt. Due to the process of adaptation to changes of adolescence, many times, they have not developed the ability to deal with certain situations yet.